GluN2B-Containg NMDA Receptors on Adult-Born Granule Cells Contribute to the Antidepressant Action of Fluoxetine - Tannenholz, Lindsay; Hen, René; Kheirbek, Mazen A. (Frontiers in Neuroscience, 2016)
Ablation of adult neurogenesis in mice has revealed that young adult-born granule cells (abGCs) are required for some of the behavioral responses to antidepressants (ADs), yet the mechanism by which abGCs contribute to AD action remains unknown. During their maturation process, immature neurons exhibit unique properties that could underlie their ability to influence behavioral output. In particular, abGCs in the DG exhibit a period of heightened plasticity 4-6 weeks after birth that is mediated by GluN2B-expressing NMDA receptors. The functional contribution of this critical window to AD responsiveness is unclear. Here, we determined the behavioral and neurogenic responses to the AD fluoxetine (FLX) in mice lacking GluN2B-containing NMDA receptors in abGCs. We found that mice lacking GluN2B exhibited an attenuated response to FLX in a neurogenesis-dependent behavioral assay of FLX action, while neurogenesis-independent behaviors were unaffected by GluN2B deletion. In addition, deletion of GluN2B attenuated FLX-induced increases in dendritic complexity of abGCs suggesting that the blunted behavioral efficacy of FLX may be caused by impaired differentiation of young abGCs.